ANALYSIS OF TEACHER PROBLEMS IN IMPLEMENTING LEARNING IMPLEMENTATION PLANS IN THE INDEPENDENT CURRICULUM AT MIN 3 MATARAM - Bahraidin (Sinar Lima, 2026)
This research is motivated by the ability of teachers to implement lesson plans under the Independent Curriculum in the classroom. MIN 3 Mataram is one of the madrasahs that has implemented the Independent Curriculum since the 2022/2023 academic year. This study used a qualitative research method with a descriptive approach. This research was conducted at MIN 3 Mataram. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. Data validity was tested through extended observation, increased persistence, source triangulation, and technique triangulation. The results of the study indicate that (1) in implementing the learning implementation plan for the independent curriculum, teachers still experience several problems, namely: (a) teachers are unable to use appropriate media and learning methods according to students' learning styles and characteristics, (b) teachers have difficulty implementing differentiated learning, (c) difficulties in implementing the Pancasila Student Profile Strengthening Project (P5), (d) teachers have difficulty managing classes according to the implementation plan. (2) Teachers' solutions to address the challenges of implementing lesson plans in the Independent Curriculum include: (a) teachers seek appropriate media and methods for students' learning styles and characteristics; (b) teachers conduct diagnostic or initial assessments to determine students' understanding, needs, and characteristics; (c) teachers consult supervisors and discuss P5 implementation challenges with trained teachers; and (d) teachers must be more flexible in developing lesson plans and adapting them to the students' classroom circumstances.